Identification of novel TACE inhibitors compatible with topical application. Issue 8 (15th April 2017) - Ouvry, Gilles; Berton, Yaël; Bhurruth-Alcor, Yushma; Bonnary, Laetitia; Bouix-Peter, Claire; Bouquet, Karine; Bourotte, Marilyne; Chambon, Sandrine; Comino, Catherine; Deprez, Benoît; Duvert, Denis; Duvert, Gwenaëlle; et al.
Graphical abstract: Abstract: Targeting the Tumor Necrosis Factor α signalling with antibodies has led to a revolution in the treatment of psoriasis. Locally inhibiting Tumor Necrosis Factor α Converting Enzyme (TACE or ADAM17) could potentially mimic those effects and help treat mild to moderate psoriasis, without the reported side effect of systemic TACE inhibitors. Efforts to identify new TACE inhibitors are presented here. Enzymatic SAR as well as ADME and physico-chemistry data are presented. This study culminated in the identification of potent enzymatic inhibitors. Suboptimal cellular activity of this series is discussed in the context of previously published results.